As trajetórias de vida das mulheres mediadas pela assistência social: a realidade da Casa Verde/SP - Ferraz, Mirela (2014)
This thesis aims to analyze the process of construction of the trajectories of women's lives mediated by the Social Welfare s Politic in the Centre of Social Welfare Refer-ence - CRAS Casa Verde, within the northern zone of São Paulo. We assume that the job of the social worker has the privilege of approaching the everyday life of those subjects. We understand that their life are conditioned by the determinants of explo-ration of the world of the work and gender oppression in the relations of production and social reproduction. To investigate on this reality is a way to strengthen these women, their families and the territory as a political struggle space. Therefore, our hypothesis focuses on understanding the mediation of social welfare women can gestate/ organize their everyday life. The research on the critical theoretical frame-work and the use of the methodology of oral history will be guided, therefore, seek to give visibility to the experience of policies subject and meanings constructed by them. Our political ethical position is to advocate the recognition of a gender perspec-tive by the Social Welfare s Politic